Influence of Auditors Scepticism on Audit Quality: Evidence from Audit Firms in Nigeria - Sani, Alfred Ilemona (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
The influence of auditors’ scepticism on audit quality has been a subject of debate regarding the robustness of audit procedure and appropriateness of audit reports on the financial statements of their clients. The study investigated the influence of auditors’ attitudes on audit quality. The aim is to examine the influence of auditors’ scepticism on audit quality. The study proxies audit scepticism using Questioning Mindset (QM), Alertness to Red Flags (ARF), Critical Evaluation of Evidence (CEE), Independence of Thought (IT) and Persistence (P) as independent variables, while audit quality is proxied by Going Concern Opinion Issuance (GCOI). Using an ex-post facto research design, data for the study were obtained via questionnaire administered to a sample of 690 respondents (115 each from six geopolitical zones of Nigeria) comprising auditors (partners, senior managers and audit trainees) from 30 audit firms (5 each from the geopolitical zones). The study adopted Partial Least Square Structural Equation Modelling (PLS-SEM) for analysing the data. Findings revealed insignificant influence of predictors on GCOI. The study recommends that audit firms in Nigeria should build cultures that encourage questioning, scepticism, and integrity over client satisfaction and strengthen client evaluation and acceptance processes to avoid high-risk or overly influential clients.